Effectiveness of in-class excel-based active learning activities for transportation engineering courses - Saha, Promothes (Frontiers in Education, 2022)
Recently, transportation engineering industry members showed concern that students lacked the skills to solve real-world engineering problems using spreadsheet data analysis. In response to the circumstances shown by industry members, this study investigated how to engage students in a better way by incorporating spreadsheet analysis during class and helping them learn the course topics. Helping students link theoretical knowledge to real-world problems can be a challenge. In this effort, in-class activities and worksheets were redesigned to integrate with Excel to solve example problems using built-in tools, including cell references, equations, data analysis tool pack, solver tool, conditional formatting, charts, etc. The effectiveness of this technique was investigated using students’ evaluations of the course, enrollment data, and students’ comments. Based on the data of those criteria, it is evident that spreadsheet activities may increase student learning.